Lithuanian Agri-Food Industry Responses to Russian Import Ban on Agricultural Products - Vlada Vitunskiene; Evaldas Serva (Institute of Economic Research (IER), 2017)
For a long time before the Russian import ban, Russia was the second most important destination for Lithuania's agricultural exports (after the EU common market), especially for processed dairy and meat products, and edible vegetables. Russia imposed a ban on most agricultural products from the EU in August 2014. Moreover, a year earlier, Russia closed its market for Lithuanian dairy products citing safety concerns. Among the EU countries, the economic impact of the Russian import ban of agricultural products may be most acute in Lithuania. Purpose of the article is to examine the Russian import ban consequences for Lithuanian agricultural products export and the agri-food industry responses to the Russian import restrictions. The examination has been based on trade and production performance indicators. Time series and spatial analysis of agricultural export flows by HS and the food production. Due to the Russian embargo Lithuania's agricultural production export worth sharply declined in 2014-2015. In volume terms, Lithuania's export of cheese, cream, yogurt and other fermented milk products was significantly lower in 2016 than in 2013, although, butter export has increased, whereas a higher share of raw milk was processed into butter. The production profile of the dairy processing industry has been changing since 2014. Processors have increased output of products like butter and skimmed milk powder which can be sold or stored within the EU intervention programs or exported to alternative markets within the EU or beyond. In 2015-2016, the export of banned agricultural products has been reoriented towards new markets. The profitability of dairy processors decreased in 2014. However, in 2015, main dairy processors increased the profitability again due to the greatly reduced farm-gate milk prices. Despite the drop of farm-gate milk prices, majority of farmers are continuing milk production. Some of the farms completely switched to local food markets
Keywords: F14; Q17; Q18; 330; agri-food products export; processing industry; Russian import ban; profitability